THE MEDIATING ROLE OF COMPANY NON-FINANCIAL PERFORMANCE AND RELIGIOSITY AS A MODERATING VARIABLE BETWEEN LEARNING ORIENTATION AND COMPANY FINANCIAL PERFORMANCE - Sanjaya, Vicky F (REVENUE: Jurnal Manajemen Bisnis Islam, 2020)
This study aims to see the mediating role of non-financial performance between learning orientation and financial performance. Furthermore religiosity has a moderating role between learning orientation and non-financial performance. No relevant profit theory and still limited research that saw the company's performance from both sides of the financial and non-financial to be a gap for doing research. The sample in this study is small and medium enterprises (SMEs) domiciled in Indonesia country. Research method using a Partial Least Square (PLS) 3. The results of this study indicate that the orientation of learning has a positive and significant impact on company financial performance and company non-financial companies. Religiosity has a moderating role strengthen the relationship learning orientation and non-financial performance. Furthermore, this study also gives results that company non-financial performance mediates some of the relationship between learning orientation to company financial performance.